Ursodeoxycholic acid in intrahepatic cholestasis of pregnancy: a secondary analysis of the PITCHES trial. (8th November 2020) - Fleminger, J; Seed, PT; Smith, A; Juszczak, E; Dixon, PH; Chambers, J; Dorling, J; Williamson, C; Thornton, JG; Chappell, LC
Abstract : Objective: To evaluate whether a particular group of women with intrahepatic cholestasis of pregnancy (ICP), based on their presenting characteristics, would benefit from treatment with ursodeoxycholic acid (UDCA). Design: Secondary analysis of the PITCHES trial (ISRCTN91918806). Setting: United Kingdom. Population or Sample: 527 women with ICP. Methods: Subgroup analyses were performed to determine whether baseline bile acid concentrations or baseline itch scores moderated a woman's response to treatment with UDCA. Main outcome measures: Bile acid concentration and itch score. Results: In women with baseline bile acid concentrations less than 40 μmol/l, treatment with UDCA resulted in increased post‐randomisation bile acid concentrations (geometric mean ratio 1.19, 95% CI 1.00–1.41, P = 0.048). A test of interaction showed no significance ( P = 0.647). A small, clinically insignificant difference was seen in itch response in women with a high baseline itch score (–6.0 mm, 95% CI −11.80 to −0.21, P = 0.042), with a test of interaction not showing significance ( P = 0.640). Further subgroup analyses showed no significance. Across all women there was a weak relationship between bile acid concentrations and itch severity. Conclusions: There was no subgroup of women with ICP in whom a beneficial effect of treatment with UDCA on bile acid concentration or itch score could be identified. This confirms that its routine use in women with this condition for improvement of bile acid concentration or itch score should be reconsidered. Tweetable abstract: PITCHES: No group of women with ICP has been found in whom UDCA reduces bile acid concentrations or pruritus. Tweetable abstract: PITCHES: No group of women with ICP has been found in whom UDCA reduces bile acid concentrations or pruritus.